Acute Spontaneous Coronary Artery Thrombosis as Initial Presentation of HIV Infection in a Young Man. (2nd March 2015) - Kayima, James; Nyakoojo, Wilson; Nakanjako, Damalie; Costa, Marco A.; Longenecker, Christopher T.; Simon, Daniel I.
Abstract : Introduction . The presentation of acute coronary syndrome (ACS) in young HIV patients may be atypical with different pathophysiological and clinical features. Acute coronary thrombosis, as a presentation of acute coronary syndrome in young patients with HIV, raises diagnostic and treatment challenges. Case Presentation . We describe a case of a 33-year-old African man, without traditional atherosclerotic risk factors, who presented with chest pain of acute onset. Emergent coronary angiography revealed extensive thrombus in the left anterior descending coronary artery with no evidence of atherosclerosis in this or other coronary vessels. Plaque and/or thrombus prolapse through the stent was noted following percutaneous coronary intervention (PCI). Resolution of chest pain and improvement in ST-segment elevation was noted after the procedure. A diagnosis of HIV infection was made during the workup for HIV infection. Conclusion . In young patients without traditional risk factors, HIV infection is a possible etiological factor for spontaneous coronary artery thrombosis. Percutaneous coronary intervention in patients with this presentation may be compounded with atherothrombotic complications. The likely pathophysiological pathway is superficial endothelial cell denudation as a result of chronic inflammation and immune activation.